PRIESTHOOD OF ALL BELIEVERS - Mitterstieler, Elmar (Asian Horizons, 2015)
All baptised believers are Priests and Kings and Prophets in their communion with Christ. But how and where do we experience this? It is a promise that is hardly ever reflected in the reality of our lives as Christians and Church members. Citing the Scripture, the Second Vatican Council has brought back into focus the promise of the inalienable equality and dignity and of the collective priesthood shared by all baptised believers. In theology and proclamation, however, this concept has been given little attention, or has even been actively avoided. This article aims to show the truth of this promise and to point out its significance for the daily lives and the liturgy of Christians. All of us, and especially those with leading functions in the Church, need to develop a greater awareness of it. Those who exercise the ministry of the Church, together with all Church members, live the one priesthood of participation in the priesthood of Jesus.